Membangun Akses Pasar dan Program Pemasaran Pelaku UMKM untuk Menyikapi Krisis Ekonomi 2023 - Annisha Suvero Suyar; Ani Murwani Muhar; Zuwina Miraza; Dody Hidayat (Forum Kerjasama Pendidikan Tinggi, 2023)
As a phenomenon, the digitalization of MSMEs in Medan Labuhan Sub-district has not properly educated MSME players who are mostly mothers who help in the family economy. By understanding the market potential, overcoming market access challenges, and utilizing government support and collaboration with other MSME players, MSMEs in Medan Labuhan Sub-district can build better market access and increase their business success. 1. Persuasive model, which is an approach that encourages and supports without coercion for the community to play an active role in this activity. 2. Community development model is an approach that involves the community directly as the subject and object of implementing community service activities. 3. Participatory Rural Appraisal (PRA) model which emphasizes community involvement in all activities starting from planning, implementing, and evaluating activity programs, and 4. The educational model is a socialization, training, and mentoring approach as a means of transferring knowledge and education for community empowerment. knowledge and infrastructure needed in aspects of determining target markets and aspects of market access and marketing strategy determination programs. The team provided assistance in digital marketing training and the creation of business accounts through e-commerce as a manifestation of the diffusion of technology used by MSME actors in conducting better buying and selling activities. increase the quantity and quality of marketing activities that are better and more directed. Meanwhile, specifically, to improve product quality in order to increase the economic value of products, the Team conducted various pieces of training and demonstrated the technicalities of virtual market access activities in front of MSME actors conduct scheduled training activities so that MSME actors can be assisted until they can manage their businesses independently.